DEVELOPMENT OF INNOVATIVE IDEAS IN IMPLEMENTATION OF LOVE CURRICULUM - M. Alang Khairun Nizar (CV. RADJA PUBLIKA, 2025)
The Ministry of Religion of the Republic of Indonesia is currently initiating the Love Curriculum, an educational initiative that aims to instill the values ​​of love for God, fellow human beings, the environment, and the nation from an early age.The method of writing the results of the review article research begins with a gap analysis followed by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The PRISMA method consists of 5 stages carried out: 1) defining eligibility criteria, 2) determining sources of information, 3) selecting data, 4) collecting data, and 5) taking data. This curriculum emphasizes four main aspects.